Digitalisasi Topeng Panji Asmorobangun Sebagai Upaya Pengembangan Pusat Kerajinan Berkelanjutan - Delijar, Ressi M.; Endrayanto, Nanang; Octavia, Nurila Shanti; Bagaskara, Arjuna Satria Dewa; Zacharias, Shofie Shafa Sabia (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
This community service program aims to support the preservation of traditional cultural arts by digitalizing the Panji Asmorobangun masks at Padepokan Asmorobangun in Malang Regency. This digitalization effort focuses on enhancing the visibility and appreciation of Malang’s traditional mask art, which faces challenges related to limited public access and engagement. Employing the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate), the program produces a digital catalog and a 3D virtual reality (VR) model of 74 Panji Asmorobangun masks. Each phase of the ADDIE model provides a systematic framework, beginning with a needs analysis of the padepokan's challenges, followed by catalog design and visual recording of the masks using PolyCam. This process yields interactive 3D representations accessible online to the public. The implementation results indicate that digitalization effectively expands the reach of traditional arts on digital platforms. Ongoing evaluations ensure the program’s sustainability. This digitalization initiative is a critical step in preserving the relevance of traditional mask art through modern technology, retaining core cultural values while inspiring sustainable efforts to preserve local cultural heritage.